Carryover effects of baloxavir acid in human nasopharyngeal/pharyngeal swabs on infectious titer testing of influenza virus. Issue 3 (28th January 2020) - Baba, Keiko; Oka, Ryoko; Shano, Shinya; Omoto, Shinya; Noshi, Takeshi; Shishido, Takao; Naito, Akira; Kawaguchi, Keiko; Ishibashi, Toru; Uehara, Takeki
Abstract: Baloxavir marboxil (BXM) demonstrated a rapid and profound decline in infectious viral titer 1 day after BXM administration. Rapid reduction in virus titer is a characteristic of BXM. There may be a possibility that drug carryover effects have impacts on the observed antiviral effects due to the poor correlation that was observed between viral titer reduction and alleviation of influenza symptoms. Here, we report possible carryover effects of baloxavir acid (BXA), an active form of BXM, on infectious titer testing. Our findings indicate that there is little impact of BXA carryover on the infectious titer testing.